Prognostic significance of hemoglobin, albumin, lymphocyte and platelet score in solid tumors: a pooled study - Li, Jinze; Zheng, Jing; Wang, Puze; Lv, Dong (Frontiers in Immunology, 2024)
ObjectiveThe high hemoglobin, albumin, lymphocyte, and platelet (HALP) score has been reported to be a good prognostic indicator for several malignancies. However, more evidence is needed before it can be introduced into clinical practice. Here, we systematically evaluated the predictive value of HALP for survival outcomes in patients with solid tumors.MethodsThis study was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Assessing the Methodological Quality of Systematic Reviews (AMSTAR) Guidelines. In March 2024, an electronic literature search was performed for articles regarding the prognostic role of HALP in solid tumors. Data from studies with reported risk ratios (HRs) and 95% confidence intervals (CIs) were pooled in a meta-analysis. Study bias was assessed using the QUIPS tool.ResultsOf the 729 articles reviewed, 45 cohorts including data from 17,049 patients with cancer were included in the pooled analysis. The pooled results demonstrated that elevated HALP score was significantly associated with favorable overall survival (HR = 0.60, 95% CI 0.54-0.67, p < 0.01), cancer-specific survival (HR = 0.53, 95% CI 0.44- 0.64, p < 0.01), progression-free survival (HR = 0.62, 95% CI 0.54-0.72, p < 0.01), recurrence-free survival (HR = 0.48, 95% CI 0.30-0.77, p < 0.01), and disease-free survival (HR = 0.72, 95% CI 0.57-0.82, p < 0.01). Subgroup analyses based on various confounding factors further revealed the consistent prognostic impact of HALP on overall survival in patients with solid tumors.ConclusionsOur findings suggest that high HALP is associated with better survival outcomes in patients. The HALP score is a potential prognostic biomarker in solid tumors, but it needs to be further studied whether it can improve the established prognostic model.